2015
DOI: 10.1186/s12938-015-0105-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of the circle of Willis in internal carotid artery stenosis and anatomical variations: a computational study based on a patient-specific three-dimensional model

Abstract: BackgroundThe aim of this study is to provide better insights into the cerebral perfusion patterns and collateral mechanism of the circle of Willis (CoW) under anatomical and pathological variations.MethodsIn the current study, a patient-specific three-dimensional computational model of the CoW was reconstructed based on the computed tomography (CT) images. The Carreau model was applied to simulate the non-Newtonian property of blood. Flow distributions in five common anatomical variations coexisting with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 75 publications
3
43
0
Order By: Relevance
“…An idealized model could be a simple one based on limited geometric parameters [47], a local 3D geometry coupled with 0D artery tree at inlet and outlets [48], or a structure rebuilt from the in-vitro model [49,50]. More patient-specifically, some idealized models were reconstructed from the central lines extracted from the clinical imaging of intracranial arteries [51][52][53] or an intact arterial structure starting from the aorta [5], or derived from changing the topology of CoW reconstructed from patientspecific CT images [54]. In-vivo geometric models were reconstructed exactly from the patient-specific imaging data.…”
Section: ) Methods To Improve Accuracymentioning
confidence: 99%
“…An idealized model could be a simple one based on limited geometric parameters [47], a local 3D geometry coupled with 0D artery tree at inlet and outlets [48], or a structure rebuilt from the in-vitro model [49,50]. More patient-specifically, some idealized models were reconstructed from the central lines extracted from the clinical imaging of intracranial arteries [51][52][53] or an intact arterial structure starting from the aorta [5], or derived from changing the topology of CoW reconstructed from patientspecific CT images [54]. In-vivo geometric models were reconstructed exactly from the patient-specific imaging data.…”
Section: ) Methods To Improve Accuracymentioning
confidence: 99%
“…The ACoAA is a vital collateral pathway of the circle of Willis as well as a preferential site of the IA [42]. Inter-hemispheric blood flow through the ACoAA and the reversed blood supply in the ACA-A1 provided critical collateral blood supply to the anterior cerebral circulation when unilateral ICA stenosis occurred [24,43]. Our previous studies have shown that in the situation of PCoA absence, the collateral flow in ACoAA changes non-linearly with the unilateral ICA stenosis degree due to the collateral mechanism [24,25].…”
Section: Modeling Considerationsmentioning
confidence: 99%
“…Inter-hemispheric blood flow through the ACoAA and the reversed blood supply in the ACA-A1 provided critical collateral blood supply to the anterior cerebral circulation when unilateral ICA stenosis occurred [24,43]. Our previous studies have shown that in the situation of PCoA absence, the collateral flow in ACoAA changes non-linearly with the unilateral ICA stenosis degree due to the collateral mechanism [24,25]. Therefore, instead of considering the region of UIAs alone in the computational domain [44][45][46], modeling the whole anterior circulation would be more appropriate to provide better insight into the hemodynamics change in ACoAA during ICA revascularization.…”
Section: Modeling Considerationsmentioning
confidence: 99%
See 2 more Smart Citations